The Impact of Supervisor Support on Preschool Teachers’ Resignation Intention in Guangzhou, China: The Mediating Role of Occupational Stress - Wang, Jie; Zhang, Qingfang; Ye, Yan (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
The issue of occupational stress among early childhood teachers has become an international research issue, support from supervisors maybe an important factor influencing teachers' professional stress and resignation intensions. To analyze the impact of supervisor support on the kindergarten teachers' resignation intention and to explore the mediating role of occupational stress in the relationship between leader support and the resignation intention of kindergarten teachers, the author selected 326 kindergarten teachers from 33 kindergartens in Guangzhou as the respondents of the survey and used the Occupational Stress Questionnaire, the Resignation Tendency Questionnaire and the Supervisor Support Questionnaire to conduct the survey. The results showed that the correlation coefficient between teachers’ perception of supervisor support and occupational stress was -0.363, p=0.000<0.05, and the correlation coefficient between the perception of supervisor support and resignation intention was -0.476, p=0.000<0.05, both of which were significantly correlated, but the correlation coefficient between occupational stress and resignation intention was 0.074, p=0.180>0.05, which was not significantly correlated. Occupational stress partially mediated the relationship between supervisor support and resignation intention. Although the results of the study showed that there was no significant correlation between occupational stress and the resignation intension, the sense of supervisor support of early childhood teachers was significantly and negatively related to occupational stress and resignation intension, indicating that occupational stress is not a key factor causing employees to quit their jobs, and decision makers consider the influence brought by interpersonal relationships and colleague support in kindergarten management activities to reduce teachers' occupational stress resignation intension by increasing the level of supervisor support.